2018
DOI: 10.14740/jocmr3209w
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ongoing Vitamin D and Low-Fat Milk Intake on Bone Metabolism in Female High-School Endurance Runners

Abstract: BackgroundVitamin D and calcium are essential nutrients for bone health. In addition, vitamin D suppresses inflammatory cytokines and increases bone resorption. Therefore, improvements in bone health by calcium and vitamin D supplementation have the potential to not only improve calcium metabolism but also suppress inflammation associated with exercise training. The purpose of this study was to determine whether ongoing vitamin D supplementation and low-fat milk intake by female high-school endurance runners w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…In this research, the results indicated that 12 weeks of vitamin D supplementation, despite optimizing vitamin D concentration, had no significant effect on IL-8, hs-CRP, and TNF-α levels in athletes. These findings regarding TNF-α levels are in agreement with the observations of Lewis [ 37 ], Zebroska [ 34 ], and Ikedo [ 36 ]. These results are inconsistent with the proposed association between vitamin D and inflammation in athletes and healthy adults [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this research, the results indicated that 12 weeks of vitamin D supplementation, despite optimizing vitamin D concentration, had no significant effect on IL-8, hs-CRP, and TNF-α levels in athletes. These findings regarding TNF-α levels are in agreement with the observations of Lewis [ 37 ], Zebroska [ 34 ], and Ikedo [ 36 ]. These results are inconsistent with the proposed association between vitamin D and inflammation in athletes and healthy adults [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Lewis [ 37 ] indicated that an insignificant relationship was observed between the level of vitamin D and inflammatory cytokines. On the other hand, in a study conducted on a group of university athletes and recreational runners, the amount of α-TNF decreased after vitamin D consumption [ 21 ], while other studies have found a negative correlation between 25 (OH)D concentration and TNF-α levels during a 24 h recovery period [ 34 , 36 ]. In addition, the levels of inflammatory markers in soccer players were investigated [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased consumption of calcium, vitamin D, and protein may play a preventative role against stress fracture development. (5, 6, 14, 1720) Prospective studies including only females showed that increased intake of calcium and vitamin D supplements, dietary calcium, or dairy products (calcium, vitamin D, and protein) were associated with decreased incidence of stress fractures (13, 21, 22).…”
Section: Discussionmentioning
confidence: 99%
“…A supplement containing 300 mg per day of calcium cannot reduce bone loss in the lumbar spine and greater Trochanter, but 600–900 mg per day can be beneficial. Also, Ikedo et al [43] on Long-distance running women showed that taking vitamin D supplementation and low-fat milk for 6 months improved bone metabolism by maintaining the concentration of 25OH-D and decreasing concentration of PTH and reducing inflammatory cytokines. Furthermore, Rajatanavin et al [38] stated that calcium supplementation of 500 mg per day can reduce bone turnover and decrease bone mass in older women.…”
Section: Discussionmentioning
confidence: 99%